Possibilities and Problems in the Development of Forensic Nursing in Japan: A Questionnaire Survey of Clinical Nurses - KODAMA, Hiromi; YANAI, Keiko; TSUNEMATSU, Kayoko (Journal of UOEH, 2012)
Forensic nursing scientifically obtains and preserves the criminal damage from victims of domestic violence, child abuse, elder abuse, sexual violence and other related forms of violence. This was developed in North America in the 1980s, and has carried out appropriate nursing care while protecting the human rights of victims. Serious crime in Japan has been increasing, and it would seem that forensic nursing opportunities should expand as well. However, in Japan, there hasnʼt been much discussion about forensic nursing. Theorizing that support for clinical forensic nursing should be recognized and relevant, we carried out a survey of 581 clinical nurses to investigate the development of forensic nursing in Japan. 93 clinical nurses (16.0%) had a low level of familiarity with forensic nursing; however, 324 nurses (56.3%) had encountered patients who had suffered violence. 264 nurses (45.4%) had a feeling of wanting to be involved in forensic nursing, but were not confident with the knowledge and technology, while 144 nurses (24.8%) were concerned about the larger responsibility they would have. 400 nurses (68.8%) hoped to receive specialized knowledge and technical education. It is necessary to establish an education system for forensic nursing in accordance with the educational status-quo while considering the present state of forensic nursing education.